Trái phiếu xanh trong thị trường chứng khoán toàn cầu - Nguyễn Khắc Quốc , Bảo; Lê , Văn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This study investigates the co-movements between the global green bond and the stock market. To further analyze the role of green bond in the global securities market, the authors assess the portfolio including representative assets, those are, S&P Green Bond Index and S&P Global 100. The authors employ MGARCH models with the conditional correlation mechanism to explore the nexus between return series from 31 May 2012 to 17 June 2022. The authors find statistically significant evidence of the positively mutual impacts between return series, which is best suited to explain under the ADCC-GARCH model. In relation, the authors find that green bond plays a tremendous role in the assessed portfolio due to their optimal holding weight of 88.53%, generating a 0.73% daily risk-adjusted return and a 0.9416 hedging effectiveness ratio. A supportive assessment reveals that the optimal holding weight of green bond increased from 86.73% during stable economic conditions to 94.05% during the occurring global volatility.